1999
DOI: 10.1046/j.1365-3040.1999.00486.x
|View full text |Cite
|
Sign up to set email alerts
|

Observations and model simulations link stomatal inhibition to impaired hydraulic conductance following ozone exposure in cotton

Abstract: Ozone (O 3 ) inhibits plant gas exchange and productivity. Vapour phase (g s ) and liquid or hydraulic phase (K) conductances to water flux are often correlated as both change with environmental parameters. Exposure of cotton plants to tropospheric O 3 reduces g s through reversible short-term mechanisms and by irreversible long-term disruption of biomass allocation to roots which reduces K. We hypothesize that chronic effects of O 3 on gas exchange can be mediated by effects on K without a direct effect of O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 62 publications
3
17
0
Order By: Relevance
“…Lower hydraulic conductance decreases the efficiency of water and nutrient transport to the canopy, limits carbon accumulation and plant growth, affects plant water relations, and can negatively affect plant survival during drought (Sperry et al , Sack and Holbrook , Woodruff et al ). Consistent with our data, eO 3 has been shown to inhibit hydraulic conductance of cotton plants ( Gossypium hirsutum ) and results in a reduction of the leaf water potential, especially during periods of high transpirational demand such as at midday (Grantz et al , Grantz ). If O 3 ‐treated plants face water‐stressed conditions, a decline in hydraulic conductance implies not only a decrease in leaf water potential (Ψ leaf ) but also a reduced ability to return to pre‐drought physiological functioning (Brodribb and Cochard , Pangle et al ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Lower hydraulic conductance decreases the efficiency of water and nutrient transport to the canopy, limits carbon accumulation and plant growth, affects plant water relations, and can negatively affect plant survival during drought (Sperry et al , Sack and Holbrook , Woodruff et al ). Consistent with our data, eO 3 has been shown to inhibit hydraulic conductance of cotton plants ( Gossypium hirsutum ) and results in a reduction of the leaf water potential, especially during periods of high transpirational demand such as at midday (Grantz et al , Grantz ). If O 3 ‐treated plants face water‐stressed conditions, a decline in hydraulic conductance implies not only a decrease in leaf water potential (Ψ leaf ) but also a reduced ability to return to pre‐drought physiological functioning (Brodribb and Cochard , Pangle et al ).…”
Section: Discussionsupporting
confidence: 91%
“…Stomatal conductance ( g s ) often has a strong positive correlation with hydraulic conductance of the soil‐leaf continuum and thus changes in g s as a result of O 3 exposure could be accompanied by modifications in liquid‐phase water transport (Brodribb et al , Sack and Frole ). For instance, some studies on cotton ( Gossypium barbadense L.) found that chronic O 3 exposure simultaneously caused reductions in g s as well as reduction in whole‐plant and root hydraulic conductance expressed on per leaf area basis (Grantz et al , Grantz and Yang ). Moreover, the apparent changes in plant size, biomass and allometric relationships induced by O 3 can potentially cause remarkable changes in hydraulic architecture at the whole‐plant level due to the strong influence of plant allometric scaling on plant water supply and demand relations (Meinzer , Mills et al ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the anisohydric oaks had lower g ref in elevated O 3 regardless of different water regimes, whereas an O 3 ‐induced increase of m was found only in WS condition. The lower g ref with no change of m might be explained by an O 3 ‐induced reduction of hydraulic conductivity due to impairment of root function (Grantz, Zhang, & Carlson, ). Our previous results obtained in the same experiment showed that Q. ilex changed the anatomical structure of thin transport roots in the combination of 1.4 × AA and WW (Mrak et al, ); mean root vessel diameter in WW plants of Q. ilex was decreased by O 3 , resulting in a reduction of hydraulic conductivity in roots.…”
Section: Discussionmentioning
confidence: 99%
“…; Meinzer & Grantz ; Grantz & Yang ; Grantz et al . ; Meinzer ). Reduced allocation to roots in this cultivar has been linked with reduced translocation of carbohydrates from source leaves (Grantz & Farrar , ).…”
Section: Discussionmentioning
confidence: 99%